1991
DOI: 10.1353/aad.2012.0554
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Family Communication Choices

Abstract: The selection of a mode of communication by members of a family with a deaf child is a critical decision in the life of that family since it will condition how the family will be able to function in the future. However, while some writers have considered the outcomes of this decision, there is little information on factors that influence the decision. The purpose of this study was to examine why families developed one pattern of communication rather than another. The data came from the parents of 192 deaf adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Young et al also suggested that caregivers' abilities to make informed choices for their children with hearing loss is greatly impacted by both the nature of the information that they receive for this purpose and the actual conception of what informed choice means for these caregivers. Caregiver difficulty with decision making was also identified by Kluwin and Gaustad (1991), who suggested delineating decisions that were conscious and those that were default (a course of action that is followed as a result of no decision being made by the caregiver).…”
Section: Influences On Decisions Regarding Communication Modementioning
confidence: 99%
See 2 more Smart Citations
“…Young et al also suggested that caregivers' abilities to make informed choices for their children with hearing loss is greatly impacted by both the nature of the information that they receive for this purpose and the actual conception of what informed choice means for these caregivers. Caregiver difficulty with decision making was also identified by Kluwin and Gaustad (1991), who suggested delineating decisions that were conscious and those that were default (a course of action that is followed as a result of no decision being made by the caregiver).…”
Section: Influences On Decisions Regarding Communication Modementioning
confidence: 99%
“…Eight studies were identified in which the authors specifically set out to examine how caregivers of children with hearing loss made decisions about communication (see Table 1; Borum, 2012;Decker, Vallotton, & Johnson, 2012;Guiberson, 2013;Kluwin & Gaustad, 1991;Watson, Hardie, Archbold, & Wheeler, 2008;Wheeler, Archbold, Hardie, & Watson, 2009). Some of these studies examined influences on decision making related to a specific child characteristic (e.g., children using cochlear implants, described in Wheeler et al, 2009) or type of influence (e.g., culture, as in Borum, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the fact that most hearing parents who do sign are limited to relatively concrete conversation probably becomes increasingly important as their child matures and needs and wants explanations for more complex social and emotional issues. During this time, it is mothers tend who tend to take on the key role in family communication (Kluwin & Gaustad, 1991Kluwin & Stinson, 1993), being more likely to learn to sign and thus more frequent than fathers in their communications with their 798 C. VACCARI and M. MARSCHARK deaf children (Gregory & Hindley, 1996;Marschark, 1997).…”
Section: Implications Of Sharing or Not Sharing A Languagementioning
confidence: 99%
“…Which method of communication to use with deaf children has been an area of contention for more than 200 years. Research has shown that the largest single influence on the mode of communication a mother chooses is related to the child's degree of hearing loss (Kluwin, Gaustad & Gonter, 1991).…”
Section: Language Development Of Deaf Childrenmentioning
confidence: 99%